Cultural heritage tourism as a catalyst of urban regeneration: the case of the historic city of Manama, Bahrain - Fatema Shubbar (23073115) (2025)
Various historic cities in the Gulf have experienced advanced decline and degradation, causing the erasure of their traditional urban fabric. In response, many Gulf countries have initiated urban regeneration projects that leverage cultural heritage for tourism and economic diversification. However, these projects face significant challenges in balancing cultural heritage conservation with tourism development. While historic Manama faces an imminent need for redevelopment, this study examines its revitalization potential while avoiding the pitfalls of previous projects in the Gulf region. This paper addresses a fundamental question: How can historic Manama be redeveloped for tourism without losing its identity? This study uses a mixed methods approach, including fieldwork and comparative case studies of urban revitalization projects in the Gulf. The findings highlight Manama’s rich cultural assets, such as its diverse religious landscape, multicultural identity, vernacular architecture, and intangible heritage, which can be leveraged to foster vibrant living heritage. Gentrification and lack of authenticity are key risks associated with many redevelopment projects in the region. This study advocates for a paradigm shift in Manama that mitigates these challenges through heritage-led redevelopment, adaptive reuse and community participation. The study contributes to the growing discourse on urban regeneration and cultural heritage tourism in the Gulf. Other Information Published in: Journal of Tourism and Cultural Change License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/14766825.2025.2565594